2015
DOI: 10.1093/ehjci/jev012
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of coronary flow reserve in patients with ischaemic and non-ischaemic cardiomyopathy and its association with clinical outcomes

Abstract: Impaired coronary vascular function, as assessed by reduced CFR by PET imaging, is common in patients with both ischaemic and non-ischaemic cardiomyopathy and is associated with MACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 27 publications
3
70
1
2
Order By: Relevance
“…37) Coronary anatomy and myocardial blood flow are the major determinants of clinical symptoms and survival in patients with epicardial coronary artery. 37,38) LVEF and HDL were found to be relatively benign predictors for postprocedural suboptimal flow despite the presence of other factors in STEMI patients. Although previous studies found a significant relationship between preprocedural TIMI flow and enzymatic infarct size and predischarge EF, 18,39) this study showed that postprocedural TIMI flow related with predischarge LVEF.…”
Section: Discussionmentioning
confidence: 92%
“…37) Coronary anatomy and myocardial blood flow are the major determinants of clinical symptoms and survival in patients with epicardial coronary artery. 37,38) LVEF and HDL were found to be relatively benign predictors for postprocedural suboptimal flow despite the presence of other factors in STEMI patients. Although previous studies found a significant relationship between preprocedural TIMI flow and enzymatic infarct size and predischarge EF, 18,39) this study showed that postprocedural TIMI flow related with predischarge LVEF.…”
Section: Discussionmentioning
confidence: 92%
“…Similarly, Majmudar et al[12] showed that a composite event of cardiac death, heart failure hospitalization, aborted sudden death or late revascularization was two-fold higher in individuals with non-ischemic cardiomyopathy and CFR ≤ 1.65 compared to CFR >1.65.…”
Section: Dilated Cardiomyopathymentioning
confidence: 99%
“…Quantification of regional MBF and CFR by PET may identify microvascular dysfunction, better characterize the extent and severity of CAD in multi-vessel disease, detect balanced decreases of MBF in all major coronary artery vascular territories, and provide prognostic information beyond regional myocardial ischemia [82,83]. Reduced CFR is a typical feature of a cardiomyopathic heart as a consequence of microvascular dysfunction even in the absence of epicardial CAD [84,85]. Outcome studies have supported microvascular dysfunction as an independent contributing factor to the symptoms and progression of heart failure and reduced CFR was a predictor of adverse cardiac events in ischemic and dilated cardiomyopathy [84,85].…”
Section: Myocardial Perfusionmentioning
confidence: 99%